Through-Thickness Properties of Composite Thin Shell Booms - Ayres, Henry (Cranfield University, 2022)
The deployment of lightweight composite booms has been a feature of the space industry for 50+ years to alter a spacecrafts geometry in space. Traditional deployment techniques have used stored strain energy, inflatables, or rotary electric motors to control the change in geometry. These composite thin shell booms are similar to a carpenter's tape measure in the way they coil in a housing and then extend from it. The composite thin shell booms are approximately ⅓ mm thick and are composed of a [±45f/0/±45f] carbon fibre epoxy laminate. Their mechanical properties are key to their successful deployment, in particular, their relaxation over time in storage before launch can result in deployment issues. This work aims to evaluate the through-thickness properties of composite thin shell booms. Finite element analysis was performed to investigate the deformation of the composite under out-of-plane loading and has been validated by performing a sensitivity analysis on the mechanical property inputs. Experimental work has also been undertaken to evaluate the through-thickness compressive young's modulus of composite thin shell booms and their through-thickness viscoelastic properties. This includes dynamic interferometric measurements of the composite to out-of-plane compressive loading. This work has evaluated the through-thickness properties of composite thin shell booms and constructed a material model of them.
Keywords: Deployable structure; Ultra-thin composite; Viscoelastic properties; DSDS22; DSDS22 Poster